Rejecting white distraction: a critique of the white logic and white methods in academic publishing. Issue 8 (20th June 2020) - Buggs, Shantel Gabrieal; Sims, Jennifer Patrice; Kramer, Rory
ABSTRACT: This critical reply engages in a critique of the prominence of "white logic" and "white methods" (Zuberi, Tukufu, and Eduardo Bonilla-Silva, eds. 2008. White Logic, White Methods: Racism and Methodology . Lanham, MA: Rowman & Littlefield) in academic publishing. We assess how the construction and proliferation of white knowledge(s) shapes analysis and interpretation, argumentation, peer review, and ultimately, publication. We call for a rejection of what we name "white distraction" and encourage the academic community to move toward more inclusive and decolonial modes of thinking, reviewing, and publishing.